Water Uptake and Germination of Caper (Capparis spinosa L.) Seeds - María Laura Foschi; Mariano Juan; Bernardo Pascual; Núria Pascual-Seva (Agronomy, 2020)
Caper is a perennial deciduous sub-shrub that grows in almost all circum-Mediterranean countries. The specialized literature presents three possible dormancy types that can cause low germination of caper seeds: Physiological dormancy (PD), physical dormancy (PY), and combinational dormancy (PY + PD). We conducted three experiments to analyze the imbibition, viability, and germination of seeds of different ages, provenances, and the level of deterioration of the seed cover. None of the commercialized lots of standard seeds tested exceeded 6% germination, nor 35% viability, while the owned seeds reached 90% in both parameters, indicating that all viable seeds germinated. The seed moisture content along the soaking period followed the first two phases of the typical triphasic model of water uptake in seed germination: The imbibition and lag phases (phase I and II of germination, respectively). Seed hydration began through the hilar region. The fact that all viable owned seeds germinated, together with their moisture content being lower than that of standard seeds, indicated that caper seeds do not have a water-impermeable coat sensu stricto, i.e., they do not show PY; nevertheless, the need to use gibberellic acid to obtain high germination percentages, demonstrated the presence of PD.